N-Heterocyclic Carbene-Catalyzed Acylalkylation of Indole via C–C Bond Cleavage/Dearomatization to Access the Multisubstituted Benzopyrrolizidinones - Xie, Ying; Li, Haiping; Hu, Xin; Lai, Yinlong (Synlett, 2025)
The development of novel approaches to construct benzopyrrolizidinones skeleton under metal-free conditions remains a significant challenge in medicinal chemistry. Therefore, we report an efficient methodology for construction of multisubstituted benzopyrrolizidinones via N-heterocyclic carbene-catalyzed acylalkylation reactions of indoles, involving C–C bond cleavage and dearomatization. This method exhibits the broad scope, excellent diastereoselectivity, allowing for formation of multisubstituted benzopyrrolizidinones under mild conditions. Moreover, N-heterocyclic carbene-catalyzed acylalkylation of Indole was further applied to the late-stage functionalization of pharmaceutical skeletons.
Keywords: Benzopyrrolizidinones; N-heterocyclic carbenes; Dearomatization